V 1162 Ori: A multiperiodic delta Scuti star with variable period and amplitude - Arentoft, T.; Sterken, C.; Handler, G.; Freyhammer, L. M.; Bruch, A.; Niarchos, P.; Gazeas, K.; Manimanis, V.; van Cauteren, P.; Poretti, E.; Dawson, D. W.; Liu, Z. L.; et al. (Astronomy and Astrophysics, 2001)
We present the results of multisite observations of the delta Scuti star V 1162 Ori. The observations were done in the period October 1999-May 2000, when 18 telescopes at 15 observatories were used to collect 253 light extrema during a total of 290 hours of time-series observations. The purpose of the observations was to investigate amplitude and period variability previously observed in this star, and to search for low-amplitude frequencies. We detect, apart from the main frequency and its two first harmonics, four additional frequencies in the light curves, all with low amplitudes (1-3 mmag). Combining the present data set with data obtained in 1998-99 at ESO confirms the new frequencies and reveals the probable presence of yet another pulsational frequency. All five low-amplitude frequencies are statistically significant in the data, but at least one of them (f5) suffers from uncertainty due to aliasing. Using colour photometry we find evidence for a radial main frequency (f1), while most or all low-amplitude frequencies are likely non-radial. We show that the main frequency of V 1162 Ori has variable amplitude and period/phase, the latter is also displayed in the O-C diagram from light extrema. The amplitude variability in our data is cyclic with a period of 282 d and a range of nearly 20 mmag, but earlier amplitude values quoted in the literature cannot be explained by this cyclic variation. O-C analysis including data from the literature show that the period of V 1162 Ori displays a linear period change as well as sudden or cyclic variations on a time scale similar to that of the amplitude variations. Based on observations obtained at the South African Astronomical Observatory (SAAO), Athens University and Kryonerion Observatories, European Southern Observatories (ESO: applications ESO 62H-0110, 64H-0065 and 64L-0182), Laboratório Nacional de Astrofísica (Brazil), Xinglong, Beersel Hills, Ege University, San Pedro Martir, Merate, Mt. Laguna, Siding Spring, Sierra Nevada, Braeside and Lick Observatories. Table 2 is only available in electronic form at the CDS via anonymous ftp to cdsarc.u-strasbg.fr (130.79.128.5) or via http://cdsweb.u-strasbg.fr/cgi-bin/qcat?J/A+A/374/1056
Keywords: methods: data analysis; STARS: INDIVIDUAL: V 1162 ORIONIS; Stars: Variables: delta Scuti; techniques: photometric